Juridical Analysis of the Process of Terminating Investigations Against Perpetrators of Traffic Accidents that Result in Death (Karimun Police Research Study) - Delviane, Annisa; Fadjriani, Lia; Jihad, Kaspol; Fadlan, Fadlan; Prasetyasari, Christiani (CV. Rayyan Dwi Bharata, 2023)
Termination of an investigation is an official action taken by law enforcement authorities, such as the police or prosecutors, to stop the investigation or investigation process into a criminal case. An investigation termination order or SP3 by the Police is a notification letter from the investigator to the public prosecutor that the investigation of the case has been stopped. This research discusses the process of legal regulation of terminating investigations of perpetrators of traffic accidents that result in death which are regulated in Article 109 paragraph (2) of the Criminal Code Law Number 22 of 2009 concerning Traffic and road transportation and to find out the implementation obstacle factors and obstacles as well as solutions to stopping investigations into perpetrators of traffic accidents that result in death. This research is a type of empirical research that uses primary and secondary data sources and analyzes the data using qualitative analysis to then form sentence descriptions that can be easily understood by readers. Based on the research results, the reasons for stopping the investigation into the perpetrator of a traffic accident which resulted in death was that there was peace between the families of the victim and the perpetrator. The investigation was stopped for purely humanitarian reasons and the culture of the people who do not want a complicated process and tend to choose peaceful paths. The process of terminating the investigation of the reporter and the reported party against the perpetrator of a traffic accident that resulted in death is for the police to use their discretionary authority and Standard Operating Procedures for restorative justice. The obstacle experienced by investigators in the process of handling this case is that witnesses do not want to appear at the police to provide information regarding the occurrence of a criminal act, because if there are no witnesses the process of handling the case will definitely be difficult to carry out.